1988
DOI: 10.1111/j.1600-0773.1988.tb00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Changes in Rat Serotonergic and Adrenergic Systems and in Receptor Responsiveness to Subchronic Desipramine Treatment

Abstract: Noradrenergic (NA) and serotonergic (5-HT) receptor profiles were compared in the cerebral cortex of young adult (3 months old) and aged (24 months old) male Sprague Dawley rats. Beta and alpha-1 receptors were significantly decreased in 24 month old rats, whereas alpha-2 receptors remained unchanged. 5-HT-2 Postsynaptic receptors and 5-HT high affinity uptake were reduced in aged animals; on the other hand the number of 3H-imipramine (3H-IMI) recognition sites located on serotonin nerve terminals and labelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…It is interesting to note that similar results have been obtained in the cerebral cortex of aged animals (Brunello et al, 1988) and in the frontal cortex of aged volunteers (Severson et al, 1985). This further supports the hypothesis that circulating lymphocytes and platelets are a convenient tissue and a readily accessible model to study human neurotransmitter receptor systems since changes in these peripheral cells may reflect alterations in receptor responsiveness in a less accessible target tissue as the brain.…”
Section: Discussionsupporting
confidence: 73%
“…It is interesting to note that similar results have been obtained in the cerebral cortex of aged animals (Brunello et al, 1988) and in the frontal cortex of aged volunteers (Severson et al, 1985). This further supports the hypothesis that circulating lymphocytes and platelets are a convenient tissue and a readily accessible model to study human neurotransmitter receptor systems since changes in these peripheral cells may reflect alterations in receptor responsiveness in a less accessible target tissue as the brain.…”
Section: Discussionsupporting
confidence: 73%
“…Enhanced 5-HT turnover (Moretti et al, 1987) and a reduction in 5-HT affinity (Brunello et al, 1988) have been reported. Relevant to the HPA axis, 5-HT receptors in the hypothalamus undergo changes in affinity with advanced age (Halpern et al, 1989).…”
Section: Introductionmentioning
confidence: 97%
“…Radioligand-binding studies in rat brain have demonstrated that there is a decrease in the number of serotonin receptors, including 5-HT 2 receptors, as the animals age (Allen et al 1983;Brunello et al 1988). There is also increased turnover of serotonin and a reduction in serotonin high-a¦nity uptake (Brunello et al 1988).…”
Section: Discussionmentioning
confidence: 98%
“…There is also increased turnover of serotonin and a reduction in serotonin high-a¦nity uptake (Brunello et al 1988). Thus, there is evidence to suggest that the senescence-related dysfunction of the serotonergic system may contribute to the age-related increase seen in the amount of rat neocortical HVSs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation